Evaluasi UX E‑Perpus UNUD Menggunakan UEQ (User Experience Questionnaire) - Komang Andika Putra; I Wayan Santiyasa (Jurnal Nasional Teknologi Informasi dan Aplikasinya, 2025)
The e-Perpus UNUD system serves as a digital library platform for managing academic documents at Udayana University. Previous studies using WebQual 3.0 and 4.0 methods reported suboptimal results, particularly in interface and user interaction quality. To provide a deeper and more emotional perspective on user experience, this study adopts the User Experience Questionnaire (UEQ) to evaluate the system across six UX dimensions: Attractiveness, Perspicuity, Efficiency, Dependability, Stimulation, and Novelty. Data were collected from 24 student respondents using the official UEQ format, and results were analyzed using the UEQ Data Analysis Tool. The findings show that Perspicuity and Dependability indicated slightly positive perceptions, while the remaining dimensions, especially Novelty, indicated negative perceptions. This study suggests a user interface redesign focusing on improving innovation, visual appeal, efficiency, and user stimulation, with future research encouraged to increase the sample size for more stable results.